Epstein-Barr virus associated diseases: an update - Pathmanathan, R. (College of Pathologists, Academy of Medicine Malaysia, 1993)
The Epstein-Barr virus (EBV), traditionally linked etiologically with infectious mononucleosis (IM), endemic Burkitt lymphoma (BL) and nasopharyngeal carcinoma (NPC) has in recent years been associated with a host of other conditions. Viral strategies for entry into cells and persistence, as well as various molecular mechanisms involved in latency, replication and transformation have been elucidated. EBV termini analysis has demonstrated the essentially clonal nature of BL, NPC and preneoplastic lesions of the nasopharynx. Strain variation between isolates of EBV suggests that differences in epithelial cell tropism among strains may exist. Treatment of EBV-associated syndromes is largely supportive although antivirals may play a role in the management of oral hairy leukoplakia. At the present time, the development of an effective vaccine remains a viable proposition.